Предмет: Алгебра,
автор: мура20031
упростите выражение (а-6) (а+6) (36+а^2)–(а^2-18)^2 и найдите его значение при а=–16
Ответы
Автор ответа:
0
(a-6)(a+6)(36+a^2)-(a^2-18)^2=(a^2-36))(36+a^2)-(a^4-36a^2+324)=a^4-1296-a^4-36a^2-324= -1620-36a^2= -1620-36(-1/6)^2= -1620-36(1/36)= -1620-1= -1621
Похожие вопросы
Предмет: Алгебра,
автор: ksusha08101974
Предмет: Математика,
автор: receptnarodnye
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: shajdullinazau1
Предмет: Математика,
автор: мак17